An overcorrection framing effect. (4th July 2019) - Seta, John J.; Seta, Catherine E.; McCormick, Michael
Abstract: With the "typical" attribute framing manipulation, assimilation effects have often been obtained; people often judge the attributes of a judgmental target more positively when the attributes are framed positively (e.g., 99% pure) than negatively (e.g., 1% impure). Research has not, however, explored or demonstrated the effects of correcting or overcorrecting for the frame's influence. Overcorrection framing occurs when a more positive response is produced by the negative frame. Across three experiments, overcorrection as well as typical framing effects were obtained. In Experiments 1 and 2, overcorrection effects were obtained when participants were prompted to consider complementary information and, in Experiment 3, when the frame's source was described as untrustworthy. In contrast, typical framing effects were obtained when prompts were not supplied and when the frame's source was not described as being untrustworthy. These results supported the unification model that uses a priming analysis to account for assimilation (typical framing) and contrast (overcorrection framing) effects. We discussed how overcorrection is expected with other framing manipulations, such as risky‐choice framing. We provided reasons for asymmetrical correction effects and discussed implications of our analysis for holistic/analytical as well as System 1/System 2 processing styles, the influence of different amounts of cognitive resource allocations, and the possibility of a correction process involving averaging.